The Uncoupling Proteins: A Systematic Review on the Mechanism Used in the Prevention of Oxidative Stress - Jonathan Hirschenson; Emiliano Melgar-Bermudez; Ryan J. Mailloux (MDPI AG, 2022)
Mitochondrial uncoupling proteins (UCP) 1-3 fulfill many physiological functions, ranging from non-shivering thermogenesis (UCP1) to glucose-stimulated insulin release (GSIS) and satiety signaling (UCP2) and muscle fuel metabolism (UCP3). Several studies have suggested that UCPs mediate these functions by facilitating proton return to the matrix. This would decrease protonic backpressure on the respiratory chain, lowering the production of hydrogen peroxide (H2O2), a second messenger. However, controlling mitochondrial H2O2 production to prevent oxidative stress by activating these leaks through these proteins is still enthusiastically debated. This is due to compelling evidence that UCP2/3 fulfill other function(s) and the inability to reproduce findings that UCP1-3 use inducible leaks to control reactive oxygen species (ROS) production. Further, other studies have found that UCP2/3 may serve as Ca2+. Therefore, we performed a systematic review aiming to summarize the results collected on the topic. A literature search using a list of curated keywords in Pubmed, BIOSIS Citation Index and Scopus was conducted. Potentially relevant references were screened, duplicate references eliminated, and then literature titles and abstracts were evaluated using Rayyan software. A total of 1101 eligible studies were identified for the review. From this total, 416 studies were evaluated based on our inclusion criteria. In general, most studies identified a role for UCPs in preventing oxidative stress, and in some cases, this may be related to the induction of leaks and lowering protonic backpressure on the respiratory chain. However, some studies also generated evidence that UCP2/3 may mitigate oxidative stress by transporting Ca2+ into the matrix, exporting lipid hydroperoxides, or by transporting C-4 metabolites. Additionally, some showed that activating UCP1 or 3 can increase mitochondrial ROS production, even though there is still augmented protection from oxidative stress. Conclusion: Overall, most available studies demonstrate that UCPs, particularly UCP2/3, prevent oxidative stress. However, the mechanism utilized to do so remains elusive and raises the question that UCP2/3 should be renamed, since they may still not be true "uncoupling proteins".